PENGARUH DAYA TOLAK PERASAN SERAI WANGI (Cymbopogon nardus) TERHADAP GIGITAN NYAMUK Aedes aegypti - Rofirma Manurung; Indra Chahaya; Surya Dharma (Lingkungan dan Kesehatan Kerja, 2013)
Effect of thrust fragrant lemongrass (Cymbopogon nardus) against bites of Ae.aegypti mosquito. Vector of Dengue Fever (DHF) is a Ae.aegypti mosquito could can be eradicated by spraying insecticide, which give impack for the environment. Alternative insecticides which are safe for the envinronment may come from plants.  Fragrant lemongrass (Cymbopogon nardus) is a mosquito repellent plant by producing Olea volatilia that serve as mosquito repellent. This research aims to dentify effect fragrant lemongrass (Cymbopogon nardus) as a repellent against bites of Ae.aegypti mosquito. The consentration fragrant lemongrass used were 1%, 2%, 3%, 4%. This reseach is a quasi experimental study with completely randomize design. The material test was the extract of fragrant lemongrass. Sampel of the research was adult Ae.aegypti mosquito, each box was using 10 mosquitos for control and 10 mosquitos for different consentration and they were repeated for 3 times. The result from the research was the number of Ae.aegypti bite on consentration of 1% were 2 mosquitos, on consentration of 2% was 1 mosquito, on consentration of 3% and 4% were none  mosquito bite. Effect of the fragrant lemongrass to Ae.aegypti mosquito bite after spraying of the extract fragrant lemongrass on rabbits showed that the power of protection on consentration of 1% and 2% was 75% to 88%, while power of protection on consentration of 3% and 4% of 100%. The result of Anova test showed that there was the significant difference on the mosquito to bite on various treatment consentration and extended with Post Hoc test gave impact difference result away different consentration. The consentration of 3% and 4% of the extract very effective as fragrant lemongrass repellent because of having  power of protection 100%. Key words: fragrant lemongrass (Cimbopogon nardus), mosquito Ae.aegypti